PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syabania, Aliza; Nurmilah, Risma (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study is to determine how much influence corporate social responsibility and intellectual capital have on financial performance. Data collection techniques in this study using secondary data collection data. Data analysis techniques in this study used descriptive statistics, t test and f test. The results of this study indicate that partially corporate social responsibility has no effect on financial performance with a t-test result of 0.243 with a significance of 0.810, the variable intellectual capital has an effect on financial performance with a t-test result of 3.082 with a significance of 0.004. Corporate social responsibility and intellectual capital simultaneously affect financial performance with an f test result of 5.733 with a significance value of 0.007. Based on the results of partial analysis, the CSR variable on financial performance with the result that it has no effect on financial performance but CSR must still be disclosed and distributed to maintain environmental stability, as well as to maintain conduciveness by the company. An increase in this category is expected to have an impact on stakeholder trust which will affect the financial performance of the company. It is also expected to maximize intellectual capital so that it can improve the company's financial performance. owned by its employees, fulfills the company's routine processes and structures that support employee efforts to produce optimal intellectual performance and maintain harmonious relationships with partners, both reliable and quality suppliers, the government and with local communities. The higher the ROA value, the more efficiently the company uses its assets in increasing its profits.